2019
DOI: 10.3389/fimmu.2019.02298
|View full text |Cite
|
Sign up to set email alerts
|

The Diverse Function of PD-1/PD-L Pathway Beyond Cancer

Abstract: The recent success of PD-1 and PD-L1 blockade in cancer therapy illustrates the important role of the PD-1/PD-L1 pathway in the regulation of antitumor immune responses. However, signaling regulated by the PD-1/PD-L pathway is also associated with substantial inflammatory effects that can resemble those in autoimmune responses, chronic infection, and sepsis, consistent with the role of this pathway in balancing protective immunity and immunopathology, as well as in homeostasis and tolerance. Targeting PD-1/PD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
226
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(259 citation statements)
references
References 187 publications
2
226
1
1
Order By: Relevance
“…Another well-known mechanism of primary resistance to immunotherapy is the upregulation of immune checkpoint molecules on tumor cells. One such immunosuppressive molecule, programmed death-ligand 1 (PD-L1), binds to the inhibitory programmed death 1 (PD-1) receptor on T cells and inhibits their activation and cytotoxic functions [92]. Interestingly, PD-L1 is now considered to be a target gene of HIF-1α and HIF-2α, indicating a crucial role of intratumoral hypoxia in the regulation of this immunosuppressive ligand [93][94][95][96].…”
Section: Hypoxia-mediated Primary Resistancementioning
confidence: 99%
“…Another well-known mechanism of primary resistance to immunotherapy is the upregulation of immune checkpoint molecules on tumor cells. One such immunosuppressive molecule, programmed death-ligand 1 (PD-L1), binds to the inhibitory programmed death 1 (PD-1) receptor on T cells and inhibits their activation and cytotoxic functions [92]. Interestingly, PD-L1 is now considered to be a target gene of HIF-1α and HIF-2α, indicating a crucial role of intratumoral hypoxia in the regulation of this immunosuppressive ligand [93][94][95][96].…”
Section: Hypoxia-mediated Primary Resistancementioning
confidence: 99%
“…It is suggested that an importance function of IL-10 in ATL may be inhibitory activities on macrophages and Th1and also as a means of escaping host defenses. It has been implicated that the negative regulatory programmed death-1/programmed death-ligand 1 (PD-1/PD-L1) pathway has an important role in the induction of CTL exhaustion during chronic viral infection and tumor (30)(31)(32). According to previous studies, suppression of immune responses and CTLs exhaustion lead to progression of disease to ATLL (33).…”
Section: Discussionmentioning
confidence: 99%
“…PDL1 encoding PD-L1. Considering, the PD-L1-programmed cell death protein 1 axis plays a critical role in the induction of Treg cells as well as being involved in immune evasion, 73 the observation that helminth PCF did not upregulate PDL1 gene expression suggests that other immune evasive mechanisms might be employed by A. suum.…”
Section: Discussionmentioning
confidence: 99%